Motion Picture Paradise : A History of Florida's Film and Television Industry. - Morton, David (University Press of Florida, 2024)
This book is a sweeping story of filmmaking in Florida, chronicling the state's importance to producers throughout 125 years by looking at the many iconic films and television shows made across the peninsula.
Description based upon print version of record.
Keywords: Motion picture locations -- Florida -- History.; Motion picture industry -- Florida -- History.; Florida -- In motion pictures.; Extérieurs (Cinéma) -- Floride -- Histoire.; Cinéma -- Industrie -- Floride -- Histoire.; SOCIAL SCIENCE / Media Studies.; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); Motion pictures.; Motion picture locations.; Motion picture industry.; Florida.; Media, entertainment, information & communication industries.; Media Studies.; History.